2006
DOI: 10.1021/bi052480i
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Protein Kinase CK2 Substrate Indicates CK2 Is Not Directly Stimulated by Polyamines in Vivo

Abstract: The activity of the protein kinase (CK2) is enhanced in vitro by the binding of polyamines to the CK2beta regulatory subunit. The overexpression of ornithine decarboxylase (ODC), the rate-limiting enzyme in polyamine biosynthesis, also elevates CK2 kinase activity in primary keratinocytes and tissues of K6/ODC transgenic mice. In an effort to better characterize the mechanisms by which polyamines may affect CK2 in vivo, we constructed a transfectable CK2 substrate cDNA consisting of the enhanced green fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Under some circumstances, CK2 holoenzyme-mediated phosphorylation can be stimulated by polyamines in in vitro kinase assays and by over-expression of ODC, the rate limiting enzyme of spermine synthesis, in cells [34-36]. However, in the case of caspase-3, over-expression of ODC1 did not promote its phosphorylation (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Under some circumstances, CK2 holoenzyme-mediated phosphorylation can be stimulated by polyamines in in vitro kinase assays and by over-expression of ODC, the rate limiting enzyme of spermine synthesis, in cells [34-36]. However, in the case of caspase-3, over-expression of ODC1 did not promote its phosphorylation (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Although this is the most parsimonious explanation for the results, it is also possible that the K121A mutation may otherwise affect CK2 binding. Polybasic compounds stimulate CK2 activity likely through interactions with the acid cluster on the ␤ subunit (Niefind et al, 2001) (but see Lawson et al, 2006). The presence of positive charges may result in charge shielding of the acid loop that normally inhibits CK2 activity (Niefind et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Some indication has been presented that the stimulation of CK2 activity by polyamines is attributable to an alteration of the quaternary structure of CK2 corresponding to a catalytically active conformation (Valero et al 1995). Recent elegant experiments by Lawson et al (2006) have revealed that polyamines increase total CK2 kinase activity through an increase in the steady levels of both CK2α and CK2β. Thus, these data suggest that the regulation of CK2 activity by polyamines occur through other mechanisms, as previously described.…”
Section: Activators Of Protein Kinase Ck2mentioning
confidence: 99%